Polycrystal positive electrode active material and preparation method and application thereof
By filling the outer layer of the secondary spherical particles of the ternary positive electrode active material and improving the spherical shape, the problem of poor material structure stability is solved, and the circulation and storage performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411836815.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-01
AI Technical Summary
The existing ternary positive electrode active materials have poor structural stability during the battery circulation process, resulting in cracking and powderization of secondary particles at the grain boundaries, reducing the cycling and storage performance of the battery.
A polycrystalline positive electrode active material is used, which is filled with the covering material at the grain boundaries of the primary particles in the outer layer of the secondary spherical particles, and improves the spherical shape through multiple spherification treatments, enhancing the shear resistance and structural stability of the material.
It improves the circulation and storage performance of the battery, reduces the particle breakage problem during the material's strong stirring process, and enhances the energy retention rate and high-temperature storage performance of the battery.
Smart Images

Figure CN119742329A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a polycrystalline positive electrode active material and a preparation method and application thereof. Background Art
[0002] In recent years, along with the introduction of my country's new energy strategy, the demand for lithium batteries in the power battery and energy storage system market has continued to increase. The positive electrode active material is the key link in determining the performance of lithium batteries. At present, the positive electrode active materials commonly used in power batteries are ternary positive electrode active materials and lithium iron phosphate materials. With the continuous improvement of electric vehicle's requirements for cruising range, ternary positive electrode active materials with higher energy density have gradually become the mainstream positive electrode active materials for power batteries. However, ternary positive electrode active materials have the problem of poor structural stability.
[0003] In the prior art, the structural stability problem of ternary positive electrode active materials is solved by surface coating. However, the coating is carried out on the surface of secondary particles. During the rolling process of film making, the fragile grain boundaries are easily crushed and cracked, exposing the highly active surface of primary particles. During the cycle, the lattice reciprocates to expand and contract and deform, generating stress, causing the secondary particles to crack and pulverize significantly at the grain boundaries, aggravating the side reactions of the electrolyte and the active materials, thereby reducing the cycle performance and storage performance of the battery. Summary of the invention
[0004] The main purpose of the present invention is to provide a polycrystalline positive electrode active material, which can improve the cycle performance and storage performance of the battery when applied to the battery.
[0005] The present invention also provides a method for preparing a polycrystalline positive electrode active material. The method can prepare the polycrystalline positive electrode active material and has simple process and low cost.
[0006] The present invention also provides a positive electrode sheet. Since the positive electrode sheet includes the polycrystalline positive electrode active material, the positive electrode sheet is used in a battery to improve the cycle performance and storage performance of the battery.
[0007] The present invention also provides a battery. Since the battery comprises the positive electrode sheet, the battery has excellent cycle performance and storage performance.
[0008] In a first aspect, the present invention provides a polycrystalline positive electrode active material, the polycrystalline positive electrode active material comprises secondary spherical particles, the secondary spherical particles comprise a plurality of primary particles, at least a portion of the surface of the secondary spherical particles has a coating substance, and the grain boundaries of the primary particles in the outer layer of the secondary spherical particles are filled with the coating substance;
[0009] The sphericity S of the secondary spherical particles is greater than 0.9.
[0010] The polycrystalline positive electrode active material as described above has a chemical composition as shown in Formula 1,
[0011] Li y Ni a Co b M c X d Y e O 2-f , Formula 1,
[0012] Wherein, M is Mn and / or Al, X includes at least one of Al, Mg, Zr, Sr, Y, Mo, and W, the coating element Y includes at least one of Al, Zr, Ti, W, Co, Mn, Nb, Zn, Sn, B, P, S, and Cl, 1.0≤y≤1.1, 0.5≤a≤0.8, 0≤b≤0.2, 0.2≤c≤0.4, 0<d<0.05, 0<e<0.01, and 0≤f≤0.01.
[0013] The polycrystalline positive electrode active material as described above, wherein the maximum load of the polycrystalline positive electrode active material is greater than 30 mN;
[0014] And / or, the maximum deformation displacement of the polycrystalline positive electrode active material is greater than 2.5 μm.
[0015] As described above, the average porosity of the polycrystalline positive electrode active material is 1%-5%, the porosity of the polycrystalline positive electrode active material is greater than the porosity of the outer layer of the secondary spherical particles, and the difference between the porosity of the polycrystalline positive electrode active material and the porosity of the outer layer of the secondary spherical particles is 0.5%-5%.
[0016] In the polycrystalline positive electrode active material as described above, the aspect ratio of the primary particles in the outer layer of the secondary spherical particles is less than 2.
[0017] The polycrystalline positive electrode active material as described above, after being stirred at 20000 rpm for 30 seconds, has a D50 reduction rate of less than 5%, and a Dmin reduction rate of less than 10%.
[0018] In a second aspect, the present invention provides a method for preparing the polycrystalline positive electrode active material as described above, comprising the following steps:
[0019] 1) performing a spheroidization treatment on a polycrystalline positive electrode active material precursor to obtain a first precursor having a sphericity greater than 0.8;
[0020] 2) performing a secondary spheroidization treatment on the first system including the first precursor, the first lithium source, and the dopant to obtain a mixed system;
[0021] 3) sintering the mixed system at 850° C.-1000° C. in an oxygen-containing atmosphere for 8 h-15 h to obtain an intermediate;
[0022] 4) The second system including the intermediate, the second lithium source and the coating agent is subjected to three spheroidization treatments to obtain the polycrystalline positive electrode active material.
[0023] In the preparation method as described above, the rotation speed of the first spheroidization treatment is 2000rpm-4000rpm, and the time is 30min-150min;
[0024] And / or, the secondary spheroidization treatment is carried out at a rotation speed of 1000 rpm-3000 rpm and for a time of 20 min-100 min;
[0025] And / or, the rotation speed of the three spheroidization treatments is 4000rpm-8000rpm, and the time is 100min-300min;
[0026] and / or, the molar ratio of the first precursor, the first lithium source, and the dopant is 1:(1.02-1.10):(0.001-0.01);
[0027] And / or, the molar ratio of the intermediate, the second lithium source, and the coating agent is 1:(0.001-0.1):(0.001-0.1).
[0028] In a third aspect, the present invention provides a positive electrode sheet, comprising the polycrystalline positive electrode active material as described above, and the polycrystalline positive electrode active material prepared by the preparation method as described above.
[0029] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0030] The polycrystalline positive electrode active material provided by the present invention is filled with a coating material at the grain boundaries of the primary particles in the outer layer of the secondary spherical particles, which can bond the primary particles and fill the grain boundaries, thereby reducing the corrosion of the weak grain boundaries caused by the electrolyte. The sphericity S of the secondary spherical particles is greater than 0.9, which can improve the shear resistance of the material, disperse stress, and reduce the problem of particle breakage of the material during strong stirring. When applied to batteries, the cycle performance and storage performance of the batteries can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 This is a cross-sectional SEM image of the polycrystalline positive electrode active material prepared in Example 1 of the present invention;
[0033] Figure 2 This is a cross-sectional SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2 of the present invention;
[0034] Figure 3 (a) is a surface SEM image of the polycrystalline positive electrode active material prepared in Example 1 of the present invention after being stirred at 20000 rpm for 30 seconds;
[0035] Figure 3 (b) is a surface SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2 of the present invention after being stirred at 20000 rpm for 30 seconds;
[0036] Figure 4 (a) is a partially enlarged SEM image of the cross section of the polycrystalline positive electrode active material prepared in Example 1 of the present invention;
[0037] Figure 4 (b) Figure 4 (a) Locally enlarged SEM image of the grain boundary filling area;
[0038] Figure 4 (c) is a SEM-EDS image of Al element distribution of the polycrystalline positive electrode active material coating material prepared in Example 1 of the present invention;
[0039] Figure 4 (d) is a SEM-EDS image of the Ni element distribution of the non-coated material of the polycrystalline positive electrode active material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In a first aspect, the present invention provides a polycrystalline positive electrode active material, comprising secondary spherical particles, wherein the secondary spherical particles comprise a plurality of primary particles, wherein a coating material exists on at least a portion of the surface of the secondary spherical particles, and the grain boundaries of the primary particles in the outer layer of the secondary spherical particles are filled with the coating material; the sphericity S of the secondary spherical particles is greater than 0.9, for example, it can be 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or a range consisting of any two of them.
[0042] It can be understood that the sphericity S in the present invention refers to the degree to which the shape of the secondary spherical particles is similar to that of a sphere. The closer the particles are to a sphere in appearance, the closer their sphericity S is to 1. It can be calculated by taking the average value of the ratio of the area of multiple cross-sections of the secondary spherical particles to the area of their circumscribed circles. Specifically, the cross-section of the secondary spherical particles can be marked with a circumscribed circle, and the area of the circumscribed circle can be calculated; then the actual area of the cross-section can be divided by the area of the circumscribed circle to obtain a sphericity. The same method is used to calculate 20 sphericities of the same sample and the average value is taken to obtain the sphericity S of the secondary spherical particles.
[0043] The primary particles in the outer layer of the secondary spherical particles in the present invention refer to the primary particles in the outermost area area, in which the SEM image of the cross-section of the secondary spherical particles is evenly divided into four regions according to the area of the circumscribed circle, and the primary particles in the outer layer are coated on the surface of the primary particles in the inner layer. The grain boundaries of the primary particles in the outer layer of the secondary spherical particles in the present invention are filled with coating materials, and the sphericity S of the secondary spherical particles is greater than 0.9. When applied to batteries, the cycle performance and storage performance of the battery can be improved. It is speculated that the higher sphericity of the secondary spherical particles can significantly improve the shear resistance of the polycrystalline positive electrode active material, improve the particle strength, disperse the stress, reduce the particle breakage problem of the polycrystalline positive electrode active material in strong stirring, and reduce the local structural deterioration caused by the tip reaction. At the same time, the grain boundaries of the primary particles in the outer layer of the secondary spherical particles are filled with coating materials, which can bond the primary particles, fill the grain boundaries, reduce the ball cracking phenomenon, and reduce the corrosion of the electrolyte on the weak grain boundaries, inhibit the penetration of the electrolyte, and complete the lithium ion transmission, thereby improving the energy retention rate of the battery and reducing the volume growth rate during high-temperature storage.
[0044] The polycrystalline positive electrode active material provided by the present invention is filled with a coating material at the grain boundaries of the primary particles in the outer layer of the secondary spherical particles, which can bond the primary particles and fill the grain boundaries, thereby reducing the corrosion of the weak grain boundaries caused by the electrolyte. The sphericity S of the secondary spherical particles is greater than 0.9, which can improve the shear resistance of the material, disperse stress, and reduce the problem of particle breakage of the material during strong stirring. When applied to batteries, the cycle performance and storage performance of the batteries can be improved.
[0045] In some embodiments of the present invention, the polycrystalline positive electrode active material has a chemical composition as shown in Formula 1,
[0046] Li y Ni a Co b M c X d Y e O 2-f , Formula 1,
[0047] Wherein, M is Mn and / or Al, X includes at least one of Al, Mg, Zr, Sr, Y, Mo, and W, the coating element Y includes at least one of Al, Zr, Ti, W, Co, Mn, Nb, Zn, Sn, B, P, S, and Cl, 1.0≤y≤1.1, 0.5≤a≤0.8, 0≤b≤0.2, 0.2≤c≤0.4, 0<d<0.05, 0<e<0.01, and 0≤f≤0.01.
[0048] For example, y can be 1.0, 1.01, 1.03, 1.05, 1.07, 1.09, 1.1, or a range consisting of any two thereof. a can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, or a range consisting of any two thereof. b can be 0, 0.05, 0.1, 0.15, 0.2, or a range consisting of any two thereof. c can be 0.2, 0.25, 0.3, 0.35, 0.4, or a range consisting of any two thereof. d can be 0.01, 0.02, 0.03, 0.035, 0.04, 0.045, or a range consisting of any two thereof. e can be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009 or a range consisting of any two thereof, and f can be 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01 or a range consisting of any two thereof.
[0049] The present invention defines the chemical composition of the polycrystalline positive electrode active material, wherein the doping element X can be selected from at least one of Al, Mg, Zr, Sr, Y, Mo, and W, and the coating element Y can be selected from at least one of Al, Zr, Ti, W, Co, Mn, Nb, Zn, Sn, B, P, S, and Cl. The coating material can be a metal oxide and / or an organic compound, and the metal oxide can include Al2O3, ZrO2, TiO2, WO3, Co3O4, MnO2, Nb2O5, B2O3, LiAlO2, Li2ZrO3, LiNbO3, LiCoO2, LiZr2(PO4)3, Li3B 11 O 18 、Li4Ti5O 12 , Li2WO6, LATP, Li2S-P2S5 (LPS), Li3InCl6, LiGeP2S5 (LGPS), Li6PS5Cl (LPSCl), Li 10 SnP2S 12 (LSnPS). The organic compound may include at least one of polyaniline (PANI), polyethylene oxide (PEG), polypyrrole (PPy), poly 3,4-ethyldioxythiophene (PEDOT), and hydroxy-terminated polydimethylsiloxane (PDMS). A higher nickel content in the polycrystalline positive active material is conducive to improving the specific capacity of the material, thereby improving the energy density of the battery. The appropriate amount of cobalt, manganese and / or aluminum content can balance the structural stability and cycle performance of the material. Doping element X and coating element Y can further enhance the thermal stability and mechanical strength of the material, reduce capacity attenuation, and optimize the conductivity and ion mobility of the material, thereby reducing the internal resistance of the battery.
[0050] In some embodiments of the present invention, the maximum load of the polycrystalline positive electrode active material is greater than 30 mN; in some embodiments, the maximum deformation displacement of the polycrystalline positive electrode active material is greater than 2.5 μm.
[0051] For example, the maximum load of the polycrystalline positive electrode active material can be 31mN, 32mN, 33mN, 34mN, 35mN, 36mN, 39mN, 40mN, 50mN, 60mN, 70mN, 80mN or any two thereof. The maximum deformation displacement of the polycrystalline positive electrode active material can be 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.5μm, 4.0μm, 5.0μm or any two thereof.
[0052] The maximum load of the polycrystalline positive electrode active material in the present invention is greater than 30mN, indicating that the polycrystalline positive electrode active material has high mechanical strength and compressive strength, which can reduce the problem of particle breakage in subsequent processing, and can also withstand large mechanical stress during the charge and discharge cycle without cracking or deformation, thereby improving the cycle life of the battery.
[0053] The maximum deformation displacement of the polycrystalline positive electrode active material in the present invention is greater than 2.5 μm, indicating that the coating material has good softness and ductility. The soft coating material can not only absorb the stress release of the material during the cycle process, reduce stress concentration and the formation of microcracks, but also maintain the integrity of the film layer when grain boundary cracking occurs, hinder the penetration of the electrolyte, thereby improving the cycle stability and safety of the battery.
[0054] In some embodiments of the present invention, the average porosity of the polycrystalline positive electrode active material is 1%-5%, the porosity of the polycrystalline positive electrode active material is greater than the porosity of the outer layer of the secondary spherical particles, and the difference between the porosity of the polycrystalline positive electrode active material and the porosity of the outer layer of the secondary spherical particles is 0.5%-5%; in some embodiments, the content of the doping element X of the secondary spherical particles is greater than the content of the doping element X of the coating material, and X includes at least one of Al, Mg, Zr, Sr, Y, Mo, and W.
[0055] Exemplarily, the average porosity of the polycrystalline positive electrode active material may be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any two thereof. The difference between the porosity of the polycrystalline positive electrode active material and the porosity of the outer layer of the secondary spherical particles may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any two thereof.
[0056] The average porosity of the polycrystalline positive electrode active material in the present invention is relatively low, which increases the contact area between the primary particles, improves the pressure resistance of the material, and enhances the material's resistance to rolling cracking during the preparation of battery pole pieces; at the same time, the lower average porosity will increase the compaction density of the material and achieve higher capacity utilization.
[0057] The porosity of the polycrystalline positive electrode active material in the present invention is greater than the porosity of the outer layer of the secondary spherical particles. The sparse structure of the outer layer of the secondary spherical particles can absorb the deformation of the material during the cycle, reduce the extension of the internal cracks of the secondary spherical particles to the outer layer, so as to alleviate the volume expansion of the material during the charge and discharge process and avoid the cracking of the material. This can improve the cycle performance and storage performance of the battery.
[0058] The difference between the porosity of the polycrystalline positive electrode active material and the porosity of the outer layer of the secondary spherical particles is small, which makes the surface of the polycrystalline positive electrode active material more compact, improves the shear resistance of the material, reduces the shedding of primary particles caused by the strong stirring process in battery preparation, and thus improves the cycle performance of the battery.
[0059] Since cracks are mainly formed in the core area, the high content of doping element M in the secondary spherical particles will refine the grains, effectively weaken the shrinkage during lithium insertion and extraction, and further even out the stress distribution inside the secondary spherical particles. During the cycle, it can withstand strain and maintain better mechanical integrity.
[0060] The sparse structure inside the secondary spherical particles and the high content of doping elements work together to disperse, reduce and absorb internal stress during the battery cycle, inhibit the generation of microcracks and pulverization, and reduce mechanical failure.
[0061] In some embodiments of the present invention, the aspect ratio of the primary particles in the outer layer of the secondary spherical particles is less than 2.
[0062] Illustratively, the aspect ratio of the primary particles of the outer layer of the secondary spherical particles may be 1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or a range consisting of any two thereof.
[0063] The primary particles in the outer layer of the secondary spherical particles in the present invention are irregular blocks and non-radially arranged, that is, randomly arranged. The outer layer structure of dense irregular blocks can improve the particle strength of the material, reduce ball cracking, and inhibit electrolyte penetration, thereby improving the cycle performance and storage performance of the battery.
[0064] The aspect ratio of the primary particles in the outer layer of the secondary spherical particles is less than 2, which can improve the conduction efficiency of electrons and ions, help reduce internal resistance, and improve the rate performance and energy density of the battery. It can also form a relatively compact stacking structure, improve the mechanical strength and structural stability of the secondary spherical particles, help maintain the integrity of the electrode during the charge and discharge cycle, reduce pulverization and shedding of electrode materials, and thus extend the service life of the battery.
[0065] In some embodiments of the present invention, after the polycrystalline positive electrode active material is stirred at 20,000 rpm for 30 seconds, the D50 reduction rate is less than 5%, and the Dmin reduction rate is less than 10%.
[0066] For example, the D50 reduction rate can be 1%, 2%, 3%, 4%, 4.5%, 4.9% or a range consisting of any two thereof. The Dmin reduction rate can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.9% or a range consisting of any two thereof.
[0067] In the present invention, the polycrystalline positive electrode active material is put into a wall breaking machine, and after stirring at 20000rpm for 30s, the polycrystalline positive electrode active material is sheared against each other, and then a particle size test is performed using a Malvern 3000 particle size analyzer. It is found that the D50 reduction rate before and after stirring is less than 5%, and the Dmin reduction rate is less than 10%, indicating that the polycrystalline positive electrode active material has good shear resistance, can improve the mechanical strength and structural stability of the material, and reduce the problem of particle breakage of the material during strong stirring. When applied to batteries, the cycle performance and storage performance of the batteries can be improved.
[0068] In a second aspect, the present invention provides a method for preparing the polycrystalline positive electrode active material as described above, comprising the following steps:
[0069] 1) performing a spheroidization treatment on a polycrystalline positive electrode active material precursor to obtain a first precursor having a sphericity greater than 0.8;
[0070] 2) performing a secondary spheroidization treatment on the first system including the first precursor, the first lithium source, and the dopant to obtain a mixed system;
[0071] 3) sintering the mixed system at 850° C.-1000° C. in an oxygen-containing atmosphere for 8 h-15 h to obtain an intermediate;
[0072] 4) The second system including the intermediate, the second lithium source and the coating agent is subjected to three spheroidization treatments to obtain the polycrystalline positive electrode active material.
[0073] In the present invention, multiple spheroidization processes are performed so that the polycrystalline positive electrode active material finally prepared has high sphericity and the coating material is evenly coated, thereby improving the shear resistance and compressive strength of the material, reducing particle breakage and primary particle shedding during the pulping and rolling processes when the material is used to prepare the electrode, thereby improving the cycle performance and storage performance of the battery.
[0074] Specifically, in step 1), the polycrystalline positive electrode active material precursor can be placed in a spheroidizer and subjected to a spheroidization treatment. The sphericity of the first precursor obtained is controlled to be greater than 0.8, which is conducive to finally obtaining a polycrystalline positive electrode active material with a higher sphericity.
[0075] In step 2), the first lithium source and the dopant are placed in a spheroidizing agent containing the first precursor, and the first system including the first precursor, the first lithium source, and the dopant is subjected to a secondary spheroidizing treatment, so that the obtained mixed system has a higher sphericity, which is convenient for obtaining an intermediate with a higher sphericity through subsequent sintering treatment. The dopant can be selected from at least one of Al2O3, Al(OH)3, MgO, Mg(OH)2, ZrO2, SrO, Y2O3, MoO3, and WO3.
[0076] In step 3), the sintering temperature can be 850°C, 870°C, 900°C, 920°C, 950°C, 980°C, 1000°C or any two thereof. The sintering time can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any two thereof. Sintering in air or oxygen atmosphere can obtain an intermediate with a higher sphericity, i.e., secondary spherical particles.
[0077] In step 4), the intermediate obtained above is cooled to room temperature and then mechanically crushed, and then the crushed intermediate, the second lithium source, and the coating agent are mixed to obtain a second system, and the second system is placed in a spheroidizer for three spheroidization treatments, the purpose of which is to coat the secondary ball particles, which can improve the coating uniformity, improve the sphericity of the particles, improve the grain boundary filling and smooth the surface of the polycrystalline positive electrode active material, improve the grain boundary corrosion resistance and compressive strength, and inhibit the side reaction of the electrode liquid.
[0078] The coating agent can be selected from Al2O3, AlOOH, ZrO2, TiO2, tetrabutyl titanate (C 16 H 36 O4Ti), WO3, H2WO4, Co3O4, Co(OH)2, MnO2, Nb2O5, SnO2, SnS2, B2O3, (NH4)3PO3, LiOH, LiN O3, LiO2, Li2S, LATP, Li2S-P2S5 (LPS), Li3InCl6, LiGeP2S5 (LGPS), Li6PS5Cl (LPSCl), Li 10 SnP2S 12 At least one of (LSnPS), polyaniline (PANI), polyethylene oxide (PEG), polypyrrole (PPy), poly 3,4-ethyldioxythiophene (PEDOT), and hydroxy-terminated polydimethylsiloxane (PDMS).
[0079] The present invention uses high heat generated by mechanical energy, such as shear force, friction force, and compaction between particles or between particles and blades, to spheroidize or coat the particles. High-energy mechanical mixing can promote frictional heat generation between the coating agent and the secondary spherical particles. During the mechanical fusion process, the high-speed rotation of the blades increases the surface temperature of the particles (including the secondary spherical particles and the coating agent). When the heat generated by the applied high mechanical energy exceeds the heat of the melting point of the coating material, the secondary spherical particles will be uniformly coated, effectively improving the coating uniformity.
[0080] In some embodiments of the present invention, the rotation speed of the first spheroidization treatment is 2000rpm-4000rpm, and the time is 30min-150min;
[0081] In some embodiments, the secondary spheroidization treatment is performed at a rotation speed of 1000 rpm to 3000 rpm and for a time of 20 min to 100 min;
[0082] In some embodiments, the three spheroidization treatments are performed at a rotation speed of 4000 rpm to 8000 rpm and for a time of 100 min to 300 min;
[0083] In some embodiments, the molar ratio of the first precursor, the first lithium source, and the dopant is 1:(1.02-1.10):(0.001-0.01);
[0084] In some embodiments, the molar ratio of the intermediate, the second lithium source, and the coating agent is 1:(0.001-0.1):(0.001-0.1).
[0085] Exemplarily, the rotation speed of the first spheroidization process can be 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or any two of them. The time of the first spheroidization process can be 30min, 50min, 70min, 100min, 120min, 150min or any two of them. The rotation speed of the second spheroidization process can be 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm or any two of them. The time of the second spheroidization process can be 20min, 30min, 50min, 70min, 100min or any two of them. The rotation speed of the third spheroidization process can be 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm or any two of them. The time of the third spheroidization process can be 100min, 150min, 200min, 250min, 300min or any two of them. The molar ratio of the first precursor, the first lithium source, and the dopant can be 1:1.02:0.001, 1:1.05:0.001, 1:1.07:0.001, 1:1.1:0.001, 1:1.1:0.005, 1:1.1:0.01, or a range consisting of any two thereof. The molar ratio of the intermediate, the second lithium source, and the coating agent can be 1:0.001:0.02, 1:0.01:0.02, 1:0.1:0.02, 1:0.1:0.001, 1:0.1:0.01, 1:0.1:0.1, or a range consisting of any two thereof.
[0086] In the present invention, three spheroidization treatments are performed, and the rotation speed of the spheroidizer (spheroidizing coating machine, KM Tech) is controlled to achieve mixing, spheroidization and coating, which can improve the sphericity and coating effect of the polycrystalline positive electrode active material, thereby improving the particle strength of the polycrystalline positive electrode active material. During the high-energy mechanical fusion process, the mutual extrusion between particles will cause the molten material to continuously penetrate the grain boundary, and finally complete the filling, modification and smoothing of the grain boundary after cooling, while improving the final sphericity of the polycrystalline positive electrode active material and reducing the tip corrosion of the material. It can also reduce the cracking of the polycrystalline positive electrode active material during the cycle process, effectively improving the mechanical integrity, thereby improving the cycle performance and storage performance of the battery.
[0087] The molar ratio of the first precursor, the first lithium source, and the dopant, as well as the molar ratio of the intermediate, the second lithium source, and the coating agent can ensure sufficient lithium supply in the material and reduce lithium defects, and the appropriate addition of the dopant can improve the conductivity, ion mobility, and structural stability of the material, thereby optimizing the performance of the battery. The appropriate coating agent can form a uniform coating material on the surface of the particles, improve the interface stability and cycle life of the material, and the appropriate addition of the first lithium source can further optimize the lithium content of the material and ensure that the battery has a high energy density.
[0088] In a third aspect, the present invention provides a positive electrode sheet, comprising the polycrystalline positive electrode active material as described above, and the polycrystalline positive electrode active material prepared by the preparation method as described above.
[0089] The positive electrode sheet of the present invention can be prepared by conventional technical means in the art. Specifically, the above-mentioned polycrystalline positive electrode active material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry, and then the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode collector. After drying, the positive electrode sheet of the present invention can be obtained.
[0090] The present invention does not particularly limit the specific types of the conductive agent and the adhesive. The conductive agent, the adhesive and other components can be selected from conventional materials in the field. For example, the conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the adhesive can be selected from one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-propylene rubber.
[0091] The present invention does not specifically limit the coating method, and any coating method such as gravure coating, extrusion coating, spraying, screen printing, etc. can be used to coat the positive electrode active layer slurry.
[0092] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0093] The battery of the present invention includes a separator, a negative electrode and an electrolyte in addition to a positive electrode sheet. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art, such as a PP film, a PE film, etc.
[0094] The battery of the present invention can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained through a stacking or winding process, and then the above-mentioned battery can be obtained through baking, liquid injection, formation, packaging and other processes.
[0095] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0096] Example 1
[0097] The method for preparing the polycrystalline positive electrode active material of this embodiment comprises the following steps:
[0098] 1) The NCM650530 precursor was placed in a spheroidizer and subjected to a spheroidization treatment at 3000 rpm for 30 min to obtain a first precursor with a sphericity of 0.93.
[0099] 2) Adding a first lithium source LiOH and a dopant Al2O3 into a spheroidizer including a first precursor, wherein the molar ratio of the first precursor, the first lithium source, and the dopant is 1:1.03:0.01, and performing a secondary spheroidization treatment at a rotation speed of 2000 rpm for 20 minutes to obtain a mixed system.
[0100] 3) The mixed system was sintered at 880°C for 12 hours in an air atmosphere to obtain an intermediate. After cooling to room temperature, the intermediate was mechanically crushed to control D50 = 12.0 ± 0.5 μm.
[0101] 4) The crushed intermediate, the second lithium source LiOH, and the coating agent Al2O3 were mixed in a molar ratio of 1:0.02:0.01 and put into a spheroidizer, and spheroidized for three times at 8000 rpm for 120 min to complete the secondary ball coating and obtain a chemical composition of Li 1.05 Ni 0.64 Co 0.05 Mn 0.29 Al 0.02 Polycrystalline positive electrode active material for O2.
[0102] Example 2
[0103] The preparation method of the polycrystalline positive electrode active material in Example 2 is basically the same as that in Example 1, except that in step 2), a first lithium source LiOH and dopants Al2O3, ZrO2, and WO3 are added to a spheroidizer including a first precursor, wherein the molar ratio of NCM650530, LiOH, Al2O3, ZrO2, and WO3 is 1:1.05:0.005:0.0005:0.0005, and a chemical composition of Li 1.07 Ni 0.64 Co 0.05 Mn 0.298 Al 0.0004 Zr 0.0004 W 0.0004 Polycrystalline positive electrode active material for O2.
[0104] Example 3
[0105] The preparation method of the polycrystalline positive electrode active material in Example 3 is basically the same as that in Example 1, except that in step 4), the crushed intermediate, the second lithium source LiNO3, and the coating agent Co(OH)2 are mixed in a molar ratio of 1:0.05:0.1 and then placed in a spheroidizer for three spheroidization treatments to obtain a chemical composition of Li 1.08 Ni 0.60 Co 0.14 Mn 0.26 Polycrystalline positive electrode active material for O2.
[0106] Example 4
[0107] The preparation method of the polycrystalline positive electrode active material in Example 4 is basically the same as that in Example 1, except that in step 4), the crushed intermediate, the second lithium source Li2S, and the coating agent SnS2 are mixed in a molar ratio of 1:0.005:0.005 and then put into a spheroidizer for three spheroidization treatments to obtain a chemical composition of Li 1.04 Ni 0.648 Co 0.05 Mn 0.299 Sn 0.004 S 0.007 O 1.993 Polycrystalline positive electrode active material.
[0108] Example 5
[0109] The preparation method of the polycrystalline positive electrode active material in Example 5 is basically the same as that in Example 1, except that the precursor used in step 1) is NCM850510, and in step 3) it is sintered at 850° C. for 12 h in an oxygen atmosphere to obtain a Li 1.05 Ni 0.83 Co 0.05 Mn 0.10 Al 0.02Polycrystalline positive electrode active material for O2.
[0110] Example 6
[0111] The preparation methods of the polycrystalline positive electrode active material in Example 6 and Example 1 are basically the same, except that in step 3), the sintering is performed at 1000° C. for 8 h.
[0112] Example 7
[0113] The preparation methods of the polycrystalline positive electrode active material in Example 7 are basically the same as those in Example 1, except that in step 3), the sintering is performed at 850° C. for 15 h.
[0114] Example 8
[0115] The preparation method of the polycrystalline positive electrode active material in Example 8 is basically the same as that in Example 1, except that the rotation speed of the first spheroidization treatment is 2000 rpm and the time is 150 min; the rotation speed of the second spheroidization treatment is 1500 rpm and the time is 80 min; the rotation speed of the third spheroidization treatment is 8000 rpm and the time is 100 min.
[0116] Example 9
[0117] The preparation method of the polycrystalline positive electrode active material in Example 9 is basically the same as that in Example 1, except that the rotation speed of the first spheroidization treatment is 3000 rpm and the time is 100 min; the rotation speed of the second spheroidization treatment is 1000 rpm and the time is 100 min; the rotation speed of the third spheroidization treatment is 5000 rpm and the time is 300 min.
[0118] Example 10
[0119] The preparation method of the polycrystalline positive electrode active material in Example 10 is basically the same as that in Example 1, except that the rotation speed of the first spheroidization treatment is 4000 rpm and the time is 50 min; the rotation speed of the second spheroidization treatment is 3000 rpm and the time is 20 min; the rotation speed of the third spheroidization treatment is 4000 rpm and the time is 100 min.
[0120] Embodiment 11
[0121] The preparation method of the polycrystalline positive electrode active material in Example 11 is basically the same as that in Example 1, except that the rotation speed of the first spheroidization treatment is 4000 rpm and the time is 30 min; the rotation speed of the second spheroidization treatment is 2000 rpm and the time is 60 min; the rotation speed of the third spheroidization treatment is 7000 rpm and the time is 150 min.
[0122] Example 12
[0123] The preparation method of the polycrystalline positive electrode active material in Example 12 is basically the same as that in Example 1, except that in step 2), a secondary spheroidization treatment is performed at a rotation speed of 800 rpm for 20 minutes.
[0124] Comparative Example 1
[0125] The preparation methods of the polycrystalline positive electrode active material in Comparative Example 1 and Example 1 are basically the same, except that in step 1), the precursor is not subjected to a spheroidization treatment.
[0126] Comparative Example 2
[0127] Comparative Example 2 is basically the same as the preparation method of the polycrystalline positive electrode active material of Example 1, except that in step 4), the crushed intermediate is mixed with the coating agent Al2O3 at a molar ratio of 1:0.002, and then sintered at 450°C for 8h to complete the coating, and a chemical composition of Li 1.05 Ni 0.646 Co 0.05 Mn 0.30 Al 0.004 Polycrystalline positive electrode active material for O2.
[0128] Test example:
[0129] 1. Sphericity: Mark the cross section of the secondary spherical particle with a circumscribed circle and calculate the area of the circumscribed circle; then divide the actual area of the cross section by the area of the circumscribed circle to get a sphericity. Calculate 20 sphericities of the same sample using the same method and take the average value to get the sphericity S of the secondary spherical particle.
[0130] 2. Maximum load and maximum deformation displacement: 10 particles were selected for nanoindentation testing until the particles were broken. Ten sets of maximum load and maximum deformation displacement data were obtained through the load-displacement curve. The maximum load and maximum deformation displacement were obtained by averaging.
[0131] 3. Porosity: The SEM image of the secondary spherical particle section is divided into four regions according to the area of the circumscribed circle by the image segmentation software Metis, where the outermost area is defined as the outer layer (e.g. Figure 1 and Figure 2 ), the porosity can be obtained by dividing the area with different contrasts in the region. The porosity of the polycrystalline positive electrode active material is the average porosity of the four regions.
[0132] 4. Aspect ratio: It is calculated by measuring the outer primary particles in the SEM image of the material cross-section.
[0133] 5. Direct current resistance (DCR): At 25°C and normal pressure (0.1MPa), the polycrystalline positive electrode active material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) of each embodiment and comparative example were fully stirred and mixed in N-methylpyrrolidone solvent at a mass percentage ratio of 95:3:2 to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil, and after drying and cold pressing, a positive electrode sheet containing a positive electrode active layer with a thickness of 100μm was obtained to prepare a soft pack battery. The soft pack battery was charged to 4.35V at a constant current of 1C, and then charged at a constant voltage of 4.35V until the current was cut off at 20mA. After standing for 5min, the voltage V1 was obtained; according to the battery capacity, 1C discharge was performed, the discharge depth was 50%, and after standing for 1h, it was discharged at a current of 5C for 10s and the corresponding voltage V2 was obtained, which was calculated by DCR=(V1-V2) / I (where I is the discharge current at 5C).
[0134] 6. High-temperature storage performance: Put the soft-pack battery before storage into water and use the drainage method to test the initial volume V0 of the soft-pack battery. Control the temperature to 70°C. After storing for 10 days, 20 days, and 30 days, respectively, use the drainage method to test the volumes V1, V2, and V3 of the soft-pack battery again. Calculate the volume changes (V1-V0) / V0, (V2-V0) / V0, and (V3-V0) / V0 to obtain the gas production during high-temperature storage.
[0135] 7. Cycle performance: According to the method in the capacity test, the polycrystalline positive electrode active material is coated into a positive electrode sheet, and the negative electrode is made of graphite, and a full battery is composed of a polyethylene separator and an electrolyte (the electrolyte is LiPF6 and the solvent is EC / DMC). Under the condition of a charge and discharge rate of 1C, the battery is cycled, and the DCR of each cycle is compared with the DCR of the first cycle to confirm the DCR growth rate. At 60°C, the DCR growth rate is calculated after 300 cycles.
[0136] At 60°C, the battery was charged to 4.35V at a constant current of 1C, then charged to 4.35V at a constant voltage of 0.5C, and then discharged to 3.0V at a discharge rate of 1C. This charge and discharge cycle was repeated 300 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 300th cycle were measured. 300 The capacity retention rate after 300 cycles is Q=Q 300 / Q1*100%.
[0137] 8. Take 300g of the polycrystalline positive electrode active materials of the embodiment and the comparative example respectively and put them into a wall breaking machine, and stir them at a fixed speed of 20000rpm for 30S to make the polycrystalline positive electrode active materials shear each other, simulating the dry electrode preparation process. Then use Malvern 3000 to perform particle size test to obtain D50, D10 and Dmin particle size data.
[0138] Figure 1This is a cross-sectional SEM image of the polycrystalline positive electrode active material prepared in Example 1 of the present invention.
[0139] from Figure 1 It can be seen that the polycrystalline positive electrode active material prepared in Example 1 of the present invention has a higher sphericity.
[0140] Figure 2 This is a cross-sectional SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2 of the present invention.
[0141] from Figure 2 It can be seen that the sphericity of the polycrystalline positive electrode active material prepared in Comparative Example 2 of the present invention is relatively low.
[0142] Figure 3 (a) is a surface SEM image of the polycrystalline positive electrode active material prepared in Example 1 of the present invention after being stirred at 20000 rpm for 30 seconds;
[0143] Figure 3 (b) is a surface SEM image of the polycrystalline positive electrode active material prepared in Comparative Example 2 of the present invention after being stirred at 20,000 rpm for 30 seconds.
[0144] from Figure 3 (a) and Figure 3 (b) It can be seen that after the polycrystalline positive electrode active material prepared in Example 1 was stirred at 20,000 rpm for 30 seconds, the reduction rates of D50 and Dmin were low, and the particle strength was relatively high; after the polycrystalline positive electrode active material prepared in Comparative Example 2 was stirred at 20,000 rpm for 30 seconds, the reduction rates of D50 and Dmin were high, and the particle strength was relatively low.
[0145] Figure 4 (a) is a partially enlarged SEM image of the cross section of the polycrystalline positive electrode active material prepared in Example 1 of the present invention.
[0146] Figure 4 (b) Figure 4 (a) Locally enlarged SEM image of the grain boundary filling area.
[0147] Figure 4 (c) is the SEM-EDS image of Al element distribution of the polycrystalline positive electrode active material coating material prepared in Example 1 of the present invention.
[0148] Figure 4 (d) is a SEM-EDS image of the Ni element distribution of the non-coated material of the polycrystalline positive electrode active material prepared in Example 1 of the present invention.
[0149] from Figure 4 (a) Figure 4 (b) Figure 4 (c) Figure 4(d) It can be seen that the polycrystalline positive electrode active material prepared in Example 1 of the present invention has coating substances on the surface of the secondary spherical particles, and the grain boundaries of the primary particles in the outer layer of the secondary spherical particles are filled with the coating substances.
[0150] Table 1
[0151]
[0152] Table 2
[0153]
[0154] It can be seen from Table 1 that, compared with the comparative example, the polycrystalline positive electrode active material provided by the present invention is filled with a coating material at the grain boundaries of the primary particles in the outer layer of the secondary spherical particles, which can bond the primary particles, fill the grain boundaries, reduce the corrosion of the weak grain boundaries caused by the electrolyte, and the sphericity S of the secondary spherical particles is greater than 0.9, which can improve the shear resistance of the material, disperse stress, and reduce the problem of particle breakage of the material during strong stirring. When applied to batteries, the cycle performance and storage performance of the batteries can be improved.
[0155] From the comparison between Examples 1-12 and Comparative Examples 1-2, it can be seen that the polycrystalline positive electrode active material provided by the present invention has higher sphericity, higher particle strength, smaller reduction rates of D50 and Dmin, and has excellent long-term gas production performance and cycle performance.
[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polycrystalline positive electrode active material, characterized in that: The polycrystalline positive electrode active material comprises secondary spherical particles, the secondary spherical particles comprise a plurality of primary particles, at least a portion of the surface of the secondary spherical particles has a coating substance, and the grain boundaries of the primary particles in the outer layer of the secondary spherical particles are filled with the coating substance; The sphericity S of the secondary spherical particles is greater than 0.
9.
2. The polycrystalline positive electrode active material according to claim 1, characterized in that: The polycrystalline positive electrode active material has a chemical composition shown in Formula 1, Li y Ni a Co b M c X d Y e O 2-f , Formula 1, Wherein, M is Mn and / or Al, X includes at least one of Al, Mg, Zr, Sr, Y, Mo, and W, the coating element Y includes at least one of Al, Zr, Ti, W, Co, Mn, Nb, Zn, Sn, B, P, S, and Cl, 1.0≤y≤1.1, 0.5≤a≤0.8, 0≤b≤0.2, 0.2≤c≤0.4, 0<d<0.05, 0<e<0.01, and 0≤f≤0.
01.
3. The polycrystalline positive electrode active material according to claim 1 or 2, characterized in that: The maximum load of the polycrystalline positive electrode active material is greater than 30mN; And / or, the maximum deformation displacement of the polycrystalline positive electrode active material is greater than 2.5 μm.
4. The polycrystalline positive electrode active material according to any one of claims 1 to 3, characterized in that: The average porosity of the polycrystalline positive electrode active material is 1%-5%, the porosity of the polycrystalline positive electrode active material is greater than the porosity of the outer layer of the secondary spherical particles, and the difference between the porosity of the polycrystalline positive electrode active material and the porosity of the outer layer of the secondary spherical particles is 0.5%-5%.
5. The polycrystalline positive electrode active material according to any one of claims 1 to 4, characterized in that: The aspect ratio of the primary particles in the outer layer of the secondary spherical particles is less than 2.
6. The polycrystalline positive electrode active material according to any one of claims 1 to 5, characterized in that: After the polycrystalline positive electrode active material is stirred at 20000 rpm for 30 seconds, the D50 reduction rate is less than 5%, and the Dmin reduction rate is less than 10%.
7. A method for preparing a polycrystalline positive electrode active material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) performing a spheroidization treatment on a polycrystalline positive electrode active material precursor to obtain a first precursor having a sphericity greater than 0.8; 2) performing a secondary spheroidization treatment on the first system including the first precursor, the first lithium source, and the dopant to obtain a mixed system; 3) sintering the mixed system at 850° C.-1000° C. in an oxygen-containing atmosphere for 8 h-15 h to obtain an intermediate; 4) The second system including the intermediate, the second lithium source and the coating agent is subjected to three spheroidization treatments to obtain the polycrystalline positive electrode active material.
8. The preparation method according to claim 7, characterized in that: The rotation speed of the first spheroidization treatment is 2000rpm-4000rpm, and the time is 30min-150min; And / or, the secondary spheroidization treatment is carried out at a rotation speed of 1000 rpm-3000 rpm and for a time of 20 min-100 min; And / or, the rotation speed of the three spheroidization treatments is 4000rpm-8000rpm, and the time is 100min-300min; and / or, the molar ratio of the first precursor, the first lithium source, and the dopant is 1:(1.02-1.10):(0.001-0.01); And / or, the molar ratio of the intermediate, the second lithium source, and the coating agent is 1:(0.001-0.1):(0.001-0.1).
9. A positive electrode sheet, characterized in that: The invention comprises the polycrystalline positive electrode active material according to any one of claims 1 to 6, or the polycrystalline positive electrode active material prepared by the preparation method according to claim 7 or 8.
10. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 9.